A study of the kinetics of copper vapour lasers - Hogan, G (1993)
A 42 mm bore, 40 W copper vapour laser (CVL) has been set up in a test rig in order to measure the values of many of the parameters of the laser as a function of time in the laser pulse-delay cycle, and of radial position in the plasma tube, while at all times running under standard operating conditions. In this way it has been possible to obtain the world's first truly comprehensive parameter map of the CVL in which all of the measurements have been performed upon the same device, operating under identical conditions and with all times accurately referenced to a datum. It is intended that this set of data is primarily for the benefit of those involved in the computer modelling of the CVL plasma, however initial analysis of the results obtained has been undertaken. All diagnostic techniques have been carefully selected as offering the highest possible level of accuracy and freedom from assumptions, and each one employed has been described in detail in terms of both theory and practical application. The hook method has been used for the measurement of the population density in the copper ground state, the upper and lower laser levels, one of the copper quartet levels, and one of the neon metastable levels, each with a time resolution of 5 ns, and a radial resolution of 2 mm. The electron density has been measured, also with a radial resolution of 2 mm and with nanosecond time resolution using a two colour interferometric technique employing the measurement of the refractive index of the plasma at 10.6 μm and 670 nm. Measurement has been made of the voltage on the laser electrodes and the current flowing in the laser during the discharge. Ancillary experiments have been performed to study the CVL discharge which have yielded some unexpected results, and measurements have been performed on a 60 mm bore CVL to determine fully the mechanism of the time delay between the onset of lasing at the plasma tube wall and on axis, and novel observations have been made.